Growth performance and antibody production in broiler chickens fed different levels of DL-methionine and L-methionine under heat stress condition - Mohd Khobib Khaisamah, Malek (2016)
The experiment was conducted to determine the growth performance and immune response based on different level of DL and L met to the broiler chickens. All birds received a standard broiler starter diet from day 1 to 21. From day 22 to 42, equal number of birds (12 cages / diet) were fed isocaloric and isonitrogenous diets with various levels of DL-Met or L-Met supplementation; (i) 0% DL-Met or L-Met (as a negative control), (ii) 0.136% DL-Met, (iii) 0.136% L-Met. (iv) 0.153% DL-Met, (v) 0.153% L-Met, (vi) 0.170% DL-Met, (vii) 0.170% L-Met, (viii) 0.187% DL-Met, (ix) 0.187% L-Met, (x) 0.204% DL-Met, or (xi) 0.204% L-Met. For each dietary group, equal numbers of birds (6 cages per diet-temperature subgroup) were subjected to unheated (23oC) or heated (32oC for 6 hours/day) condition. Heat treatment depressed feed intake (day 22-42) and body weight (day 42) but had negligible effect on feed conversion ratios (FCR) (day 22 – 42). Irrespective of temperature, birds fed the negative control diet had significantly poorer FCR (day 22 – 42) than the other groups which did not differ. The day 42 body weights of the negative control chickens and those fed diet with 0.136% DL-Met were similar. However, the former had significantly lower body weights than the other groups. Diet had no significant effect on mortality rate of unheated birds. Within the heated group, except the negative control chickens, birds fed 0.136% DL-Met had significant higher mortality than others. It can be concluded that methionine supplementation can be lower (0.136% and 0.153%) than the Cobb recommended values without any detrimental effect on growth performance of broilers. Providing excess Met had no beneficial effect. Based on mortality rate under high temperature and live weight, it appears that L-Met has higher efficacy than DL-Met. There is no significant different between antibody production based on diet treatment and heat stress condition